Korelasi antara Kecerdasan Emosional dan Gaya Belajar terhadap Prestasi Akademik Bahasa Inggris Taruna - Rossydi, Ahmad; Purbo Wartoyo, Bayu (Politeknik Penerbangan Makassar, 2018)
For an ATC, mastery of English is a very important part of their job. Before becoming an ATC, an ATC candidate must take an English proficiency test (ICAO English Language Proficiency Test) and are required to obtain the level determined by the International Civil Aviation Organization (ICAO), the international organization that regulates aviation in the world. The level determined for an ATC is in accordance with Annex 1 on Personnel Licensing which states that the minimum level for the requirements to become an ATC is level 4. In this study, the authors divided into six parts, namely research methods and design, population and samples, research instruments, data collection procedures, and data analysis techniques. The method used in this research is correlation. Correlation between emotional intelligence, learning styles, and academic achievement of English cadets’ level III ATKP Makassar. The purpose of this study was to provide descriptive information about the correlation between emotional intelligence, learning styles on English academic achievement, cadets level III ATKP Makassar. The results of the study obtained significant results between emotional intelligence, learning styles on English academic achievement, cadets’ level III ATKP Makassar